Ontology-Driven Software Development - Pan, Jeff Z; Aßmann, Uwe; Ebert, Jürgen; Staab, Steffen; Zhao, Yuting (Springer-Verlag, 2013)
This book is about a significant step forward in software development. It brings state-of-the-art ontology reasoning into mainstream software development and its languages. Ontology Driven Software Development is the essential, comprehensive resource on enabling technologies, consistency checking and process guidance for ontology-driven software development (ODSD). It demonstrates how to apply ontology reasoning in the lifecycle of software development, using current and emerging standards and technologies. You will learn new methodologies and infrastructures, additionally illustrated using detailed industrial case studies.The book will help you: Learn how ontology reasoning allows validations of structure models and key tasks in behavior models.Understand how to develop ODSD guidance engines for important software development activities, such as requirement engineering, domain modeling and process refinement.Become familiar with semantic standards, such as the Web Ontology Language (OWL) and the SPARQL query language.Make use of ontology reasoning, querying and justification techniques to integrate software models and to offer guidance and traceability supports.This book is helpful for undergraduate students and professionals who are interested in studying how ontologies and related semantic reasoning can be applied to the software development process. In addition, itwill also be useful for postgraduate students, professionals and researchers who are going to embark on their research in areas related to ontology or software engineering.